Clinico-demoghraphic Profile and Outcome of Critically Ill COVID 19 Patient Admitted in the ICU of a Tertiary Care Government Hospital in Dhaka, Bangladesh - Hossain, Md Mozaffer; Sarker, Subroto Kumar; Salim, Mohammad; Rahman, A K M Ferdous; Reza, Syed Tarik; Mohsin, Mohammad (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background & objectives: First outbreak of corona virus disease (COVID-19) started in Wuhan, Chinaat December 2019and since then, it spread globally but information about critically ill patients withCOVID-19 is still limited. The characteristic clinical observations and outcomes of this disease (COVID-19) have been reported from different countries. So, it is important to know the demographic profile andoverall outcome of COVID-19 patients. We aimed to describe the clinic-demographic characteristics andoutcome of critically ill COVID-19 patients admitted into the intensive care unit of Dhaka MedicalCollege Hospital. Methods:This prospective observational study was carried out in the COVID non-surgical IntensiveCare Unit (ICU) of Dhaka Medical College Hospital, Dhaka, Bangladesh from 2nd May to 31stDecember2020.Out of 549 suspected cases, 392 patients were found RT-PCR for COVID-19 positive and157 were diagnosed as COVID patients clinically and from HRCT of chest but RT-PCR negative includedin this study. After admission in ICU, all patients had been treated according to ICU protocol. Durationof ICU stay, data collection regarding demographic, clinical and laboratory parameters, managementand outcome of COVID-19 patients admitted in the ICU were done. Patient outcomes were recorded asdeath or survival (transferred or discharged). Results:A total of 549 patients (male 415, female 134, mean age 57.10 years) with RT-PCR for COVID-19 positive 392 and 199 clinically diagnosed covid-19 but RT-PCR negative were enrolled in this study.Regarding COVI-19 related symptoms, 98.54%(541) respiratory distress, 79.96 % (n=439) cough, 62.84%(n=345) history of fever,10.2 % (n=56) anosmia and 5.28% (n=29), lose motion. Diabetes mellitus (DM)and Hypertension was the most common co-morbidity (64.89%), Hypertension(HTN)56.46% was thesecond most common co-morbidity..For improvementof oxygenation of COVID patient, we treated 5.46%(n=30) by Non Re-breather Mask, 51.91% (n= 285) by High Flow Nasal Cannula (HFNC),14.20%(n=78)bynon invasive mechanical ventilation(BiPAP) and28.41% (n= 156) by Invasive Mechanical Ventilation.Mean duration of ICU stay were 12.33days and range of ICU staywere 1-30 days. Among 549 COVIDpatient,36.24% (n=199) were transferred to the isolation ward or discharged at home and 63.75 % (n=350)were died. Conclusion: This study showed the overall demographic and clinical features of critically ill COVID-19patients, admitted in the covid non-surgical ICU of Dhaka Medical College Hospital, the largest tertiarycare hospital in Bangladesh. As it was a single centered study, we need more study with multi centerapproach to know the detail demographic profile and outcome of COVID-19 patients. JBSA 2021; 34(1): 5-11